HUBUNGAN PENGETAHUAN DAN PERSEPSI MASYARAKAT DENGAN UPAYA PENCEGAHAN COVID-19 DI KELURAHAN SRONDOL WETAN, SEMARANG - Fatma Nur Suryaningrum; Nurjazuli Nurjazuli; Mursid Rahardjo (Jurnal Kesehatan Masyarakat (Undip), 2021)
A case of pneumonia with no known cause was found in Wuhan City, Hubei Province, China in December 2019. Until finally, the samples studied showed the etiology of the new coronavirus named Coronavirus Disease-2019 (COVID-19). This virus can be transmitted from human to human and has spread widely in China and more than 190 countries and including Indonesia. Data from the Health Office show that in the Srondol Wetan sub-district, Semarang City has the highest positive cases of COVID-19 in the Banyumanik sub-district, with 11 confirmed positive cases. This study aims to identify the relationship between public knowledge and perceptions with efforts to prevent COVID-19 in the Srondol Wetan Village, Semarang. This type of research is analytical research with a quantitative approach. The population in this study were the people of Srondol Wetan village with a sample of 120 people who were taken by purposive sampling technique. Collecting research data using a questionnaire via Google form, then analyzed using the Spearman statistical test. The results of analysis showed that there was a significant relationship between the knowledge variable and the efforts to prevent COVID-19 with p-value = 0.000. Then there is a significant relationship between perceptions and efforts to prevent COVID-19, p-value = 0.045 in Srondol Wetan Village, Semarang. The conclusion of the study is that there is a significant relationship between knowledge and perception and efforts to prevent COVID-19.